2008
DOI: 10.4049/jimmunol.180.1.464
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Clear Bacteria Associated with Parasitic Nematodes Augmenting the Development of an Effective Th2-Type Response

Abstract: Infection with the parasitic nematode Nippostrongylus brasiliensis induces a potent Th2 response; however, little is known about early stages of the innate response that may contribute to protective immunity. To examine early events in this response, chemokine expression in the draining lymph node was examined after N. brasiliensis inoculation. Pronounced increases of several chemokines, including CCL2, were observed. Compared with wild-type mice, elevations in a Gr-1bright population in the draining lymph nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 49 publications
4
32
0
Order By: Relevance
“…This is consistent with previous reports in allergy models in which type 2 cytokines are reduced in IL-17 deficient mice relative to wildtype animals [52,53]. This suggests paradoxically that IL-17 promotes type 2 responses, supported by reports in which neutrophils contribute to the subsequent type 2 response during N. brasiliensis infection [44,54]. However, as discussed below, in this same nematode model Th2 cytokines suppress IL-17A in the lung [26 ], as also reported by others [55 ,56].…”
Section: Il-17 and Type 2 Cytokinessupporting
confidence: 90%
“…This is consistent with previous reports in allergy models in which type 2 cytokines are reduced in IL-17 deficient mice relative to wildtype animals [52,53]. This suggests paradoxically that IL-17 promotes type 2 responses, supported by reports in which neutrophils contribute to the subsequent type 2 response during N. brasiliensis infection [44,54]. However, as discussed below, in this same nematode model Th2 cytokines suppress IL-17A in the lung [26 ], as also reported by others [55 ,56].…”
Section: Il-17 and Type 2 Cytokinessupporting
confidence: 90%
“…In this context our results show that allergic animals develop an effective and improved innate immune response to clear bacteria from peritoneum. This is consistent with the studies in parasitic nematode infected animals, another model of potent and highly polarized T H 2-type response, which demonstrate that neutrophils successfully clear bacteria associated with parasite nematode infections [29]. So, in conditions of T H 2 preferential polarization, animals may defend from bacterial infections supporting their innate immune response.…”
Section: Discussionsupporting
confidence: 74%
“…For many years, it was thought that emigration from tissues was only confined to lymphocytes and DCs, but not to granulocytes. Nevertheless, we and others have shown that neutrophils can migrate to LNs in response to different stimuli, such as inflammation (12)(13)(14) or infection (15)(16)(17)(18), where they shape the immune response by interacting with DCs and hence modulating Ag presentation (19). Indeed, we previously reported that, when OVA Ag is injected into hind footpads of previously OVA/CFA-immunized mice, the main OVA + cells in footpads and popliteal LNs (poLNs) are neutrophils (12).…”
mentioning
confidence: 99%